2016
DOI: 10.1097/bot.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Development of Nonunion or Delayed Healing After an Open Long Bone Fracture

Abstract: Prognostic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 22 publications
2
81
0
3
Order By: Relevance
“…Yet fracture healing can go awry in 5–10% of cases in the form of delayed or nonunion fractures (referred to collectively as DNFs) . Recent data specific to open long bone fractures indicated that 17% developed nonunion and another 8% exhibited delayed union . With delayed union the initial periosteal response ceases before fracture bridging, while nonunion involves persistent lack of bridging after intramembranous and endochondral repair have ceased .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet fracture healing can go awry in 5–10% of cases in the form of delayed or nonunion fractures (referred to collectively as DNFs) . Recent data specific to open long bone fractures indicated that 17% developed nonunion and another 8% exhibited delayed union . With delayed union the initial periosteal response ceases before fracture bridging, while nonunion involves persistent lack of bridging after intramembranous and endochondral repair have ceased .…”
mentioning
confidence: 99%
“…Patient‐dependent risk factors include older age, diabetes, smoking, nutritional deficiencies, and the use of anti‐inflammatory agents . Local infection can be particularly deleterious to fracture healing, and some components of the adaptive immune system may inhibit fracture healing . Other local factors associated with DNF include the extent of soft tissue injury, and compartment syndrome .…”
mentioning
confidence: 99%
“…Although this typical trauma cohort consist mainly of young, psychically healthy adults, comorbidities such as psychiatric disorders and characteristics as smoking were abundant and may have contributed to impaired healing [30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…1 They are mostly high velocity injuries in the young and domestic injuries due to osteoporosis in the elderly population. 1 With prompt surgical care, these fractures heal well with excellent functional results. However due to the above mentioned native bone setters, a small group of such fractures often end with non-unions.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of such non-unions still involves open reduction with internal fixation and bone grafting after freshening the fractures ends and removal of interposing soft and fibrous tissues. 1 The AO principles must still be adhered to with a pinch of salt and soft tissues must be respected. Here we present our functional assessment of 21 patients with distal femur fracture non-unions treated by open reduction and internal fixation with supplemental bone grafting.…”
Section: Introductionmentioning
confidence: 99%